A common poor fund for the metropolis - Dodd, William H. (Statistical and Social Inquiry Society of Ireland, 1881)
The Charity Organisation Committee of this Society, in their report in 1876, drew attention to the London system of having a common poor fund for the metropolitan unions, and suggested the desirability of extending this system to the Dublin unions. A reform which was commenced under Lord Palmerston's administration, and carried into effect under Lord Derby's administration, and extended by Mr. Goschen under Mr. Gladstone's administration, by the Metropolitan Poor Amendment Act, 1870, is one deserving consideration; and I propose to inquire if the principle on which it proceeded can be applied to the Dublin unions with advantage to the community.
Read before the Society, 20 April 1880
Keywords: Charity Organisation; Poor fund; Poverty; Welfare; 314.15